Hydrological Prediction Coordinates. - Vera, O.O. (2019)
The objective of this work is to show the current vices of hydrological studies consisting of the use of daily rainfall information and return time as an independent variable in the design of hydraulic structures projects related to the evacuation of rainwater from direct runoff; always citing lack of pluviographic information and confusing the historical return time with the prediction time, all of which seriously affects the sizing of said structures. With the aim of correcting such vices, information from the storm analysis and predictive return time in the probabilistic modeling process was used here. The results of the probabilistic simulation show that, for the same prediction horizon and the same period of standard duration of rainfall intensity, the value of the intensity grows very rapidly while the risk of prediction decreases and vice versa, or what is the same, the predictive return time is very sensitive to the probability of success and grows as it grows, tending rapidly to infinity; from which it follows that the prediction triad is made up of return time, risk and prediction horizon.